PENERAPAN MODEL PEMBELAJARAN DENGAN MENGGUNAKAN MEDIA PREZI UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA PADA MATA KULIAH BAHASA INGGRIS - Eka Resty Novieta Sari; Rizal Ula Ananta Fauzi (Al-Lisan: Jurnal Bahasa, 2019)
This study aims is to apply the learning model by using prezi to improve understanding of English courses. This research was conducted at the PGRI university of Madiun in the Academic Year of 2017/2018. The research subjects were students of Primary School Teacher Education. This study uses a classroom action research design (classroom action research) was used to solve learning problems in the classroom that seeks to study and reflect in depth some aspects of learning. This research was divided into two cycles that are adjusted to the time allocation and topic chosen. Based on the findings of the study, it can be concluded that the implementation of prezi media can improve understanding of English class 2B material, Primary School Teacher Education Study Program. This increase was shown by the achievement of the average understanding of the concept of the first cycle of 73 with 69% completeness and in the second cycle of 83 with 94% completeness. So it can be concluded that there has been an increase of 25%. This shows that the application of the learning model using this prezi media can improve students' understanding.